A CASE STUDY INTO READING COMPREHENSION STRATEGIES OF FOURTH YEAR FAST-TRACK STUDENTS AT FELTE, ULIS-VNU - Nguyễn, Thị Quyên (2021)
The change in language teaching from teacher-centeredness to learnercenteredness in language classroom has resulted in empirical research on the good language learners, among which is the investigation into learners‟ strategy. In Vietnamese, learners‟ chief exposure to English language is through reading, which reinforces the necessity of becoming proficient readers if they want to be a good language learner. Therefore, this research aims to explore students‟ reading comprehension strategies and find out the differences in strategy use by successful and less successful readers. Two cases from the fast-track division at FELTE, ULIS-VNU were selected for in-depth investigation. The two main instruments of data collection were think-aloud protocols and documents with the former as the main instrument. Triangulation was made between these two types of data while qualitative analysis method was employed to reach the most valid and reliable conclusions. This research yielded significant findings to proposed research questions. The successful reader took an interactive approach to the text while the counterpart approached it mostly from bottom-up. The successful reader was found to employ higher frequency of both metacognitive and cognitive strategy than the less one. More notably, active combination of cognitive strategies and interactive relationship between metacognitive and cognitive strategies were seen almost all the time in the successful reader while absent the less one. Based on these findings, implications were made for the reading classroom and language assessment. “Modeling what good readers do” and thinkaloud protocols as alternative assessment in reading class are the two significant implications of this research